ChemInform Abstract: Direct α‐Vinylidenation of Aldehydes and Subsequent Cascade: Gold and Amine Catalysts Work Synergistically. Issue 20 (20th May 2014) - Wang, Zhaofeng; Li, Xijian; Huang, Yong
Abstract The title reaction provides a rapid access to polysubstituted furans from aldehydes [reaction of (IIIa)].